Labour Market Integration, Occupational Uncertainty, and Fertility Choices in Germany and the UK - Christian Schmitt (Demographic Research, 2012)
The aim of this paper is to investigate how occupational prospects affect first-birth decisions of men and women. Contrasting the continental conservative German welfare state with the liberal market economy of the UK, the focus of analyses rests on how welfare state alignment affects fertility rationales in the context of either promising or bleak occupational prospects. The results based on data from BHPS and GSOEP show that welfare state orientations influence work-family choices, evoking a delay of family formation among British and German women with a close labour market attachment. Furthermore, a lengthy process of occupational integration tends to hamper the transition to parenthood among both men and women, and particularly in Germany.
Keywords: 330; crossnational comparison; fertility; first birth; occupational uncertainty; occupational integration; Beschäftigung; Familie; Arbeitsmarktpolitik; Vergleich; Deutschland; Großbritannien